The Association Between Antipsychotics and Bone Fragility: An Updated Comprehensive Review - Michele Mercurio; Giovanna Spina; Olimpio Galasso; Giorgio Gasparini; Cristina Segura-Garcia; Pasquale De Fazio; Renato de Filippis (Diagnostics)
Background: Antipsychotic drugs appear to be related to reduced bone mineral density (BMD). We conducted a narrative review to collect the available literature investigating the relationship between antipsychotic use and bone fragility. Methods: A review of the published literature was conducted and reported through PubMed/Scopus/Cochrane libraries. We included studies using any antipsychotic treatment where the bone metabolism, osteoporosis, and/or risk of fractures has been assessed. Results: After screening 1707 items, we finally included 15 papers. A total of 3245 initial patients were identified, of whom 1357 patients with a mean age of 43.8 years underwent antipsychotic treatment and were analyzed. The mean antipsychotic treatment duration of the treated group was 15.8 ± 13.9 years. Among the included studies, two reported a statistically significant difference in lumbar BMD reduction between the antipsychotic exposed group and the control group. Femoral neck BMD levels had been reported in four of the case–control studies; two reported a statistically significant difference in femoral neck BMD reduction between the antipsychotic exposed group and the control group. Conclusions: Prolonged use of antipsychotic treatment seems to be associated with an increased risk of reduced BMD, and, consequentially, with an augmented risk of bone fragility and fractures. This effect is not limited to vulnerable groups, such as those with significant medical comorbidities, the elderly, and postmenopausal women, but may also apply to anyone using antipsychotics in the long-term. Clinicians’ awareness of antipsychotic prescriptions should optimize their potential while reducing this risk.